Wisdom Versus Material Achievement Reflected In Dan Brown's The Last Symbol Novel (2009) : A Psychoanalytic Criticism - AZ ZAHROH., ZURAIDAH (2012)
This study attempts to explore the death instinct of the major character on his purpose of life. The objective of the research is to analyze the major character based on its structural elements and psychoanalytic perspective. In analyzing the psychoanalytic aspects, the researcher applies the theory of psychoanalysis proposed by Sigmund Freud. The researcher employs the qualitative research as the type of the research. The data sources are divide into two, primary data source and secondary data source. The primary data source is The Lost Symbol novel written by Dan Brown released in 2009. While the secondary data sources are other materials taken from books and internet related to the study. The results of this study are as follows. Firstly, Based in the structural analysis, it is evident that Dan Brown wants to deliver that wealth without wisdom is nothing. Secondly, based on the psychoanalytic analysis, Brown clearly illustrates a psychological phenomenon called death instinct in which most people in this world want to live longer. Finally, the psychoanalytic analysis shows that material achievement is nothing without wisdom.